Structural studies of the bond-orientational order and hexatic–smectic transition in liquid crystals of various compositions. Issue 17 (12th April 2017) - Zaluzhnyy, I. A.; Kurta, R. P.; Sulyanova, E. A.; Gorobtsov, O. Yu.; Shabalin, A. G.; Zozulya, A. V.; Menushenkov, A. P.; Sprung, M.; Krówczyński, A.; Górecka, E.; Ostrovskii, B. I.; Vartanyants, I. A.
Abstract : We report on the X-ray studies of freely suspended hexatic films of three different liquid crystal compounds. Abstract : We report on the X-ray studies of freely suspended hexatic films of three different liquid crystal compounds. By applying angular X-ray cross-correlation analysis (XCCA) to the measured diffraction patterns the parameters of the bond-orientational (BO) order in the hexatic phase were directly determined. The temperature evolution of the BO order parameters was analyzed on the basis of the multicritical scaling theory (MCST). Our results confirmed the validity of the MCST in the whole temperature range of the existence of the hexatic phase for all three compounds. The temperature dependence of the BO order parameters in the vicinity of the hexatic–smectic transition was fitted by a conventional power law with a critical exponent β ≈ 0.1 of extremely small value. We found that the temperature dependence of higher order harmonics of the BO order scales as the powers of the first harmonic, with an exponent equal to the harmonic number. This indicates a nonlinear coupling of the BO order parameters of different order. We demonstrate that compounds of various compositions, possessing different phase sequences at low temperatures, display the same thermodynamic behavior in the hexatic phase and in the vicinity of the smectic–hexatic phase transition.